Neuronal calcium sensor proteins: calcium sensors and regulators of diverse cellular functions - Burgoyne, Bob (Henry Stewart Talks, 2007)
Introduction to calcium sensors, The neuronal calcium sensor (NCS) protein family, The calcium/myristoyl switch, Dynamics of hippocalcin translocation, Specific localization of NCS proteins, Functions of NCS-1, Hippocalcin in synaptic plasticity, KChIP proteins in traffic of potassium channels, Molecular targets of NCS proteins, The unique features of the NCS family
Updated at 2010/11/01